2023
DOI: 10.1007/s11696-023-02854-9
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of thermal behavior of CL20ES and CL50WS steel powders used in selective laser melting

Tatiana Ivanova,
Michal Kořenek,
Miroslav Mashlan
et al.

Abstract: The phase and structural changes of steel powders CL20ES and CL50WS used in additive manufacturing were studied by Mössbauer spectroscopy and X-ray diffraction. Investigated powders were annealed in the temperature range 500 °C–1100 °C in oxidizing and inert atmosphere. Annealing in an oxidizing atmosphere resulted in the formation of different iron oxides in both steel powders depending on the annealing temperature. In addition, a phase change of ferrite to austenite was identified when annealing CL50WS steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The transmission Mössbauer spectroscopy was employed to exclude the formation of any amorphous phases and to monitor any changes in a close proximity of the Fe atoms. The fitting model for the room-temperature Mössbauer spectra included a singlet for the austenitic stainless steel and a doublet for the zinc ferrite (Figure 11a) [11,31]. The presented transmission Mössbauer spectra exhibited significant changes in the doublet's quadrupole splitting and full-width at half maximum (FWHM) (Table 2).…”
Section: The High-temperature Annealing Of Cl20es Znfe 2 O 4 Powders ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission Mössbauer spectroscopy was employed to exclude the formation of any amorphous phases and to monitor any changes in a close proximity of the Fe atoms. The fitting model for the room-temperature Mössbauer spectra included a singlet for the austenitic stainless steel and a doublet for the zinc ferrite (Figure 11a) [11,31]. The presented transmission Mössbauer spectra exhibited significant changes in the doublet's quadrupole splitting and full-width at half maximum (FWHM) (Table 2).…”
Section: The High-temperature Annealing Of Cl20es Znfe 2 O 4 Powders ...mentioning
confidence: 99%
“…It has been shown that high-temperature phase transformations can lead to the loss of stainless steel's anti-corrosive properties [10]. For example, the commercial CL20ES austenitic steel loses its stainless properties at around 700 • C [11], where intercrystallite rusting appears. The presence of chromium in the bulk does not completely prevent rust formation in the surface layer, as investigated by [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%